Efficacy, Safety And Feasibility Of Antiemetic Prophylaxis With Fosaprepitant, Granisetron And Dexamethasone In Pediatric Patients With Hemato-Oncological Malignancies - Cabanillas Stanchi KM; Ebinger M; Hartmann U; Queudeville M; Feucht J; Ost M; Koch MS; Malaval C; Mezger M; Schober S; Weber S; Michaelis S; et al. (Dove Medical Press, 2019)
Karin Melanie Cabanillas Stanchi,1,* Martin Ebinger,1,* Ulrike Hartmann,2 Manon Queudeville,1 Judith Feucht,1 Michael Ost,1 Marie-Sarah Koch,1 Carmen Malaval,1 Markus Mezger,1 Sarah Schober,1 Simone Weber,1 Sebastian Michaelis,1 Veit Lange,1 Peter Lang,1 Rupert Handgretinger,1 Michaela Döring1 1Department of General Pediatrics, Hematology/Oncology, University Children‘s Hospital Tübingen, Tübingen 72076, Germany; 2University Pharmacy, Eberhard-Karls-University of Tübingen, Tübingen 72076, Germany*These authors contributed equally to this workCorrespondence: Michaela DöringUniversity Hospital Tübingen - Children’s Hospital, Department I – General Pediatrics, Hematology/Oncology, Hoppe-Seyler-Str. 1, Tübingen 72076, GermanyTel +49-(0)7071-2981355Fax +49-(0)7071-295203Email michaela.doering@med.uni-tuebingen.deBackground: Chemotherapy-induced nausea and vomiting (CINV) are a major burden for patients undergoing emetogenic chemotherapy. International guidelines recommend an antiemetic prophylaxis with corticosteroids, 5-HT3R-antagonists and NK1R-antagonists. The NK1R-antagonist fosaprepitant has shown favorable results in pediatric and adult patients. There is little pediatric experience with fosaprepitant.Methods: This non-interventional observation study analyzed 303 chemotherapy courses administered to 83 pediatric patients with a median age of 9 years (2–17 years), who received antiemetic prophylaxis either with fosaprepitant and granisetron with or without dexamethasone (fosaprepitant group/FG; n=41), or granisetron with or without dexamethasone (control group/CG; n=42), during moderately (CINV risk 30–90%) or highly (CINV risk>90%) emetogenic chemotherapy. The two groups’ results were compared with respect to the safety and efficacy of the antiemetic prophylaxis during the acute (0-24hrs after chemotherapy), delayed (>24–120hrs after chemotherapy) and both CINV phases. Laboratory and clinical adverse events were compared between the two cohorts.Results: Adverse events were not significantly different in the two groups (p>0.05). Significantly fewer vomiting events occurred during antiemetic prophylaxis with fosaprepitant in the acute (23 vs 142 events; p<0.0001) and the delayed (71 vs 255 events; p<0.0001) CINV phase. In the control group, the percentage of chemotherapy courses with vomiting was significantly higher during the acute (24%/FG vs 45%/CG; p<0.0001) and delayed CINV phase (28%/FG vs 47%/CG; p=0.0004). Dimenhydrinate (rescue medication) was administered significantly more often in the CG, compared to the FG (114/FG vs 320/CG doses; p<0.0001). Likewise, in the control group, dimenhydrinate was administered in significantly more (p<0.0001) chemotherapy courses during the acute and delayed CINV phases (79 of 150; 52.7%), compared to the fosaprepitant group (45 of 153; 29.4%).Conclusion: Antiemetic prophylaxis with fosaprepitant and granisetron with or without dexamethasone was well tolerated, safe and effective in pediatric patients. However, larger prospective trials are needed to evaluate these findings.Keywords: fosaprepitant, granisetron, pediatric, antiemetic prophylaxis, chemotherapy induced vomiting, children